Could microRNA-146a and microRNA-223 serve as biomarkers for predicting disease activity in rheumatoid arthritis patients? - Bakay, Umut; Gulkesen, Arif; Akgol, Gurkan; Kaya, Arzu; Sen, Askin; Erol, Deniz; Gural, Yunus (Bayrakol Medical Publisher, 2026)
Aim: This study aimed to investigate the potential utility of circulating microRNA-146a and microRNA-223 as biomarkers for assessing disease activity in patients with rheumatoid arthritis (RA). Methods: Serum levels of miRNA-146a and miRNA-223 were measured in 60 RA patients and 30 healthy controls. Disease activity was assessed using the Disease Activity Score 28 (DAS28). Patients were stratified into two groups based on their treatment regimen: 30 patients on conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) and 30 patients on biologic disease-modifying antirheumatic drugs (bDMARDs). The expression levels of miRNA-146a and miRNA-223 were assessed by real-time polymerase chain reaction (RT-PCR). Results: In patients with RA, there was a significant overexpression of miRNA-146a compared to healthy controls (p<0.05). The Area Under the Curve (AUC) for miRNA-146a in serum was 0.679 (95% Confidence Interval: 0.572-0.774, p<0.001), indicating its diagnostic potential. ROC curve analysis revealed that miRNA-146a had a sensitivity of 66.67% and a specificity of 70%. Both miRNA-146a and miRNA-223 levels were found to be highest in patients with high disease activity, and their elevated levels were strongly associated with elevated CRP and DAS28 scores, both of which are indicators of systemic inflammation and disease activity in RA. Conclusion: MiRNA-146a and miRNA-223 are valuable biomarkers for assessing disease activity in RA, particularly miRNA-146a, which demonstrated good diagnostic performance.
Keywords: biomarkers; CRP; DAS-28; miRNA-146a; miRNA-223; Real-Time PCR; rheumatoid arthritis; tender joints